2010
DOI: 10.1002/jsfa.3974
|View full text |Cite
|
Sign up to set email alerts
|

Lead contamination in different varieties of tea plant (Camellia sinensis L.) and factors affecting lead bioavailability

Abstract: The results indicated that the uptake, transport and accumulation of Pb by tea plant organs were strongly governed by soil conditions and tea variety, thus providing tea producers with useful information on variety selection for the production of quality teas containing low levels of Pb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 163 publications
0
9
0
Order By: Relevance
“…The main sources of heavy metals in tea samples are their growth media and local environmental factors. Chen and others () reported that Pb availability increased significantly as the soil pH decreased. The Cu availability in soil was affected by soil pH and organic matter contents (Jin and others ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The main sources of heavy metals in tea samples are their growth media and local environmental factors. Chen and others () reported that Pb availability increased significantly as the soil pH decreased. The Cu availability in soil was affected by soil pH and organic matter contents (Jin and others ).…”
Section: Resultsmentioning
confidence: 95%
“…Qin and Chen () found that premium grade tea (tender tea) contains less Pb. Chen and others () found that different tea varieties had different abilities in uptake, translocation, and accumulation of heavy metals. This may in part explain why the trace metal concentrations in the 3 types of tea were black tea > Oolong tea > green tea.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al (2009) reported that among the tested toxic heavy metals, the most abundant metal in the tea leaves was Pb, which is of the most concern by tea drinkers, ranging between 2.28 and 5.61 mg kg − 1 among the eight cultivars. Among 41 tea plant varieties, Chen, Xu, Yu, Chen, and Shi (2010) further reported that the ratio of Pb concentration in mature leaves to that in young leaves ranged from 1.7 to 6.5 where the minimum concentration of Pb in young leaf was 1 mg kg − 1 and the maximum was 19.8 mg kg − 1 .…”
Section: Lead In Made Teamentioning
confidence: 99%
“…The main sources of heavy metals in tea such as Pb and Cd are fertilizers and local environmental factors [ 8 ]. Chen et al [ 9 ] reported that Pb availability increased significantly as the soil pH decreased. Lead enters human body mainly through oral ingestion and absorption through the gut.…”
Section: Introductionmentioning
confidence: 99%